2015
DOI: 10.1016/j.vetmic.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Genetic stability of Schmallenberg virus in vivo during an epidemic, and in vitro, when passaged in the highly susceptible porcine SK-6 cell line

Abstract: Schmallenberg virus (SBV), an arthropod-borne orthobunyavirus was first detected in 2011 in cattle suffering from diarrhea and fever. The most severe impact of an SBV infection is the induction of malformations in newborns and abortions. Between 2011 and 2013 SBV spread throughout Europe in an unprecedented epidemic wave. SBV contains a tripartite genome consisting of the three negative-sense RNA segments L, M, and S. The virus is usually isolated from clinical samples by inoculation of KC (insect) or BHK-21 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
0
12
0
2
Order By: Relevance
“…As this calf comprehensively recapitulated the gross alterations the authors had specifically associated with natural in utero infection by SBV (Bayrou and others 2014), the presence of the SBV genome was first sought by (RT)-qPCR (Bilk and others 2012, Hofmann and others 2015). The presence of segments S and L genomic RNA was ascertained in the brainstem (BS) and SC, with Ct values ranging from 31.9±0.26 (BS) to 35.4±0.52 (SC) and from 35.2±0.42 (BS) to 37.6±0.42 (SC) for the S and L segments, respectively.…”
Section: Investigationsmentioning
confidence: 99%
“…As this calf comprehensively recapitulated the gross alterations the authors had specifically associated with natural in utero infection by SBV (Bayrou and others 2014), the presence of the SBV genome was first sought by (RT)-qPCR (Bilk and others 2012, Hofmann and others 2015). The presence of segments S and L genomic RNA was ascertained in the brainstem (BS) and SC, with Ct values ranging from 31.9±0.26 (BS) to 35.4±0.52 (SC) and from 35.2±0.42 (BS) to 37.6±0.42 (SC) for the S and L segments, respectively.…”
Section: Investigationsmentioning
confidence: 99%
“…This is supported by reports of high SBV genetic stability in vector-derived SBV sequences in Poland [44]. Additionally, Hoffmann et al (2015) reported that SBV has a relatively low mutation rate both in vitro and in vivo [45]. Several field studies of virus variability have also demonstrated that the virus is relatively stable over time [46, 47].…”
Section: Introductionmentioning
confidence: 80%
“…To date, 11 full SBV genomic sequences were available in GenBank, originating from Germany, the Netherlands, and Belgium [3,12,[27][28][29]. To investigate the variability of the SBV sequences, we characterized the coding sequence of seven SBV strains collected in Hungary, including the virus from the first local case detected in 2012 (SBV-Hun4), and six additional strains from samples collected in 2014.…”
Section: Discussionmentioning
confidence: 99%